An NMR-Based Experimental Study on the Pore Structure of the Hydration Process of Mine Filling Slurry - Jielin Li; Hanwen Liu; Kaiming Ai; Longyin Zhu (Advances in Civil Engineering, 2018)
To study the evolution of porosity in the process of filling slurry hydration, samples of tailing filling with different mixing ratios and different curing ages were prepared, and the pore structure was tested by low-field nuclear magnetic resonance (LF-NMR). According to the T2 spectrum distribution curve and T2 spectrum area of the filling slurry hydration process, the porosity and the evolution of the pore distribution features of the filling samples were analysed. The results showed that the higher the mass concentration of the filling slurry, the slower the hydration reaction, the smaller the average size of the pores, the higher the proportion occupied by harmful pores, and the lower the proportion occupied by multiharmful pores. The smaller the cement-sand ratio of the slurry, the higher the proportion occupied by harmful pores and the larger the aperture of the pores. The porosity of the filling slurry with the cement-sand ratio of 1 : 8 is the highest, and the hydration velocity of the filling slurry with the cement-sand ratio of 1 : 3 is the fastest.